Qualitative Study: Pregnancy Experience of Premarital Teenage School Dropouts in Bekasi Regency Area - Mukaromah, Nahdiyatul; Muslimah, Rifa’at Hanifa; RN, Endang Purwati (West Science Interdisciplinary Studies, 2025)
Background: Premarital teenage pregnancy is a global phenomenon that has significant physical, psychological, and educational impacts. This study was conducted to explore the situation faced by teenagers who experienced pregnancy before marriage and consequently dropped out of school. Purpose: The purpose of this study is to identify the experiences, challenges, and impacts faced by premarital pregnant teenagers who drop out of school. Methods: This study employed an exploratory qualitative design using purposive and snowball sampling techniques. Participants included 20 pregnant teenagers, triangulated with 4 school teachers and 4 midwives. The study was conducted in Bekasi Regency from July to October 2024. Semi-structured interviews were carried out using a voice recorder, and the data were analyzed using Colaizzi’s Method. Results: The findings revealed five main themes: (1) unwanted pregnancy, (2) the effect of pregnancy on education, (3) support and discrimination, (4) physical and emotional impact, and (5) self-acceptance. Conclusion: This study shows that premarital teenage pregnancy leading to school dropout results in stigma, social pressure, educational disruption, and mental health challenges. Addressing this issue requires collaboration between the government, educational institutions, and the community by improving access to healthcare services and psychological counseling to support pregnant teenagers in continuing their education. Novelty: This study provides new insights into the lived experiences of premarital pregnant teenagers who drop out of school in an Indonesian context an area rarely explored in existing literature. Unlike most previous studies focusing on health outcomes, this research highlights the intersection between pregnancy, educational discontinuation, and psychosocial adjustment, offering culturally grounded evidence for designing inclusive school re-entry and adolescent reproductive health policies.